Characterization of a recurrent 15q24 microdeletion syndrome. - Sharp, A; Selzer, R; Veltman, J; Gimelli, S; Gimelli, G; Striano, P; Coppola, A; Regan, R; Price, S; Knoers, N; Eis, P; Brunner, H; et al. (2007)
We describe multiple individuals with mental retardation and overlapping de novo submicroscopic deletions of 15q24 (1.7-3.9 Mb in size). High-resolution analysis showed that in three patients both proximal and distal breakpoints co-localized to highly identical segmental duplications (>51 kb in length, > 94% identity), suggesting non-allelic homologous recombination as the likely mechanism of origin. Sequencing studies in a fourth individual provided base pair resolution and showed that both breakpoints in this case were located in unique sequence. Despite the differences in the size and location of the deletions, all four individuals share several major features (growth retardation, microcephaly, digital abnormalities, hypospadias and loose connective tissue) and resemble one another facially (high anterior hair line, broad medial eyebrows, hypertelorism, downslanted palpebral fissures, broad nasal base, long smooth philtrum and full lower lip), indicating that this represents a novel syndrome caused by haploinsufficiency of one or more dosage-sensitive genes in the minimal deletion region. Our results define microdeletion of 15q24 as a novel recurrent genomic disorder.